FORMULASI FUNGSI MASLAHAH DALAM PERILAKU KONSUMSI RUMAH TANGGA MUSLIM - SYAPARUDDIN, SYAPARUDDIN (IAIN Antasari, 2015)
Abstract: This study aims to discuss about how the function of maslahah (utility) could be fomulated inthe consumtion behavior of a house hold. The function of maslahah in the consumtion behavior isformulated as this equation: M = f ( X, Y, Bx, By). Based on this model, it could be expalained thatmaslalah is the outcome of an activity which can bring about berkah (benediction). In consequence, eachmoslem house hold will pay a big attantion to maslahah to do his economic goals. A moslem house holdwill select a good or service to consume if it will bring about berkah or not. It means that a moslemhouse hold doesnât see the utility of the good or service which he will consume only, but also berkahwhich the good or service has. The behavior of finding berkah for a moslem house hold could be seenthrough his characters such as not wastefull, paying attantion to another personâs interest, not deceivingsomeone else, and rightfull.